Transfistula Anorectoplasty (TFARP): Better Surgical Technique for the Management of Vestibular Fistula - Khan, JG; Ali, MA; Yusuf, MA; Islam, MK; Rahaman, MA; Hasina, K; Akter, J; Sharif, AR; Talukder, AR; Ahsan, AI (Journal of Shaheed Suhrawardy Medical College, 2012)
Background: Many approach have been tried for management of vestibular fistula, most of them have post operative complication like wound infection, wound dehiscence, more hospital stay which compromise the functional out come and aesthetic appearance of the perineum. Objective: The aim of present study was to see the effectiveness of Transfistula Anorectplasty (TFARP) Which was required minimal dissection without interruption of perineal body and perineal skin. Methodology: The cross sectional study on 43 patients with vestibular fistula were held in Dhaka Shishu Hospital from September 2008 to April 2010. Patients were operated after obtaining informed consent and standard bowel preparation. Data on demographics, operation time and postoperative complications were collected as a questionnaire and plotted on Microsoft Excel and analyzed systematically by SPSS version 17. Patients were followed up for a period of 2½ months postoperatively. Results: There is no statistical deference in patient population regarding age, geographical distribution, and clinical presentation. Mean operation time was 76.5 min for TFARP and 84.34 min for ASARP. Two (02) cases had wound infection after TFARP operation and 11 patients after ASARP operation. One patient develops partial wound dehiscence after TFARP and was healed after conservative treatment within 7 days. On the other hand 05 patients developed partial wound dehiscence and 04 patients developed complete wound disruption after ASARP which were also treated conservatively need more than 2 weeks on an average. Mean hospital stay were 6.45 days after TFARP operation and mean hospital stay were 7.87 days after ASARP operation. 20 neonates and infant who were treated by TFARP operation have good bowel movement without laxative and symmetrical anal contraction after stimulation. Conclusion: TFARP is an operation produce less morbidity and is more effective procedures and superior procedures than that of ASARP operation and give aesthetic appearance of the perineum. DOI: http://dx.doi.org/10.3329/jssmc.v4i1.11996 J Shaheed Suhrawardy Med Coll, 2012;4(1):10-14